Aircraft noise level study at the Sultan Ismail International Airport - Abdul Wahab, Aiza Norwani (2008)
This study emphasizes on noise level study of aircraft at the Sultan Ismail International Airport (SIIA), Senai, Johor. Aircraft noise is more significant than any other noise sources in airport and it affects people living in the vicinity and its surrounding areas. Aircraft noise which is produced during engine run-up, taxiing, take-off, approach, landing and flyover is determined by using three methods of calculation which are widely used globally. Noise and Number Index (NNI) and Equivalent Continuous Sound Level (Leq) are determined by conducting data sampling. The equipment used is Pulsar Model 64 Data Logging Sound Level Meter. Samplings are taken once at 3 various locations, within airport compound and its surrounding areas, up to 1 km radius from the center of runway for a duration of 12 hours on each station. Unit for NNI is PNdB while unit for Leq is in dB(A). The study also determines current and future Noise Exposure Forecast (NEF) values for 3 aircraft operation which are take-off, approach and flyover. Data on Effective Perceived Noise Level (EPNL) for Airbus A320-214 and Boeing 737-400 are provided by International Civil Aviation Organization (ICAO). NEF contours are also plotted for current and future conditions. All values obtained are compared to standard classification and community’s acceptability. Results show that current and future condition at the Sultan Ismail International Airport is acceptable with no prominent problem except for annoyance in airport compound. NEF contours show that the development at the SIIA and its surrounding areas are within allowable limit and boundary.